Bioinorganic chemistry : a short course - Rosette M. Roat-Malone (Hoboken, NJ : Wiley, 2020)
"This book provides the fundamentals for inorganic chemistry and biochemistry relevant to understanding bioinorganic topics. Rather than striving to provide a broad overview of the whole, rapidly expanding field, this resource provides essential background material, followed by detailed information on selected topics. The goal is to give readers the background, tools, and skills to research and study bioinorganic topics of special interest to them. To reflect current practices and needs, instrumental methods and techniques are referred to and mixed through the book instead of being a standalone chapter. In this new edition, the author expands or adds coverage of computer hardware and software, metalloenzymes, metals in medicines, and nanobioinorganic chemistry"--Provided by publisher
Keywords: Biochemistry; Chemistry, Bioinorganic